Interactive video playback and opponent assessment in lizards - Ord, Terry J; Evans, Christopher S (Behavioural processes, 2002)
Video playback has been used to explore many issues in animal communication, but the scope of this work has been constrained by the lack of stimulus–subject interaction. In many natural contexts, each participant's signalling behaviour is dependent from moment-to-moment on that of the other. Analyses of acoustic communication demonstrate the value of reproducing such social contingencies. We assessed the utility of interactive playback for studies of visual signalling by comparing the responses of male Jacky dragons, Amphibolurus muricatus, to interactive and non-interactive digital video playbacks of a life-sized conspecific. Displays produced by lizards in the interactive condition had the effect of suppressing the aggressive display of their simulated opponent. Each stimulus sequence generated during an interactive playback was subsequently played to a size-matched control animal. Males that could interact with the video stimulus responded principally with aggressive displays, while those that could not produced a mixture of aggressive and appeasement signals. Adding a degree of receiver responsiveness is hence sufficient to alter the type of signal evoked, even when video stimuli are physically identical. Interactive playback permits the experimental study of a broader range of theoretical topics and can enhance the realism of video stimuli.